Anaerobic Corrosion of 304 Stainless Steel Caused by the Pseudomonas aeruginosa Biofilm - Jia, Ru; Yang, Dongqing; Xu, Dake; Gu, Tingyue (Frontiers in Microbiology, 2017)
Pseudomonas aeruginosa is a ubiquitous bacterium capable of forming problematic biofilms in many environments. They cause biocorrosion of medical implants and industrial equipment and infrastructure. Aerobic corrosion of P. aeruginosa against stainless steels has been reported by some researchers while there is a lack of reports on anaerobic P. aeruginosa corrosion in the literature. In this work, the corrosion by a wild-type P. aeruginosa (strain PAO1) biofilm against 304 stainless steel (304 SS) was investigated under strictly anaerobic condition for up to 14 days. The anaerobic corrosion of 304 SS by P. aeruginosa was reported for the first time. Results showed that the average sessile cell counts on 304 SS coupons after 7-day and 14-day incubations were 4.8 × 107 cells/cm2 and 6.2 × 107 cells/cm2, respectively. Scanning electron microscopy and confocal laser scanning microscopy corroborated the sessile cell counts. The X-ray diffraction analysis identified the corrosion product as iron nitride, confirming that the corrosion was caused by the nitrate reducing biofilm. The largest pit depths on 304 SS surfaces after the 7-day and the 14-day incubations with P. aeruginosa were 3.9 m and 7.4 m, respectively. Electrochemical tests corroborated the pitting data.